Message Encryption Using Spinning Caesar XOR Binary Cryptography Algorithm (SPICA-XB): Message Encryption Using Spinning Caesar XOR Binary Cryptography Algorithm (SPICA-XB) - Akrilvalerat Deainert Wierfi; Agung Jasuma; Dony Ariyus (Jurnal Mantik, 2020)
Data security is a mechanism to protecting data and any attempt to impose limits on a system for access that does not have an authority (unauthorized person) causes poses a risk to valuable fan-sensitive information. To improve security in the text, images, video, and audio can be done by using two data security techniques such as cryptography and steganography. Cryptography is the process of plaintext to ciphertext randomizing using certain patterns. The secret message steganography focuses on inserting data or secret messages into other data such as text, images, video or audio. To increasing the security of data hiding, a combination of the two techniques is used wherein the initial data or message will be encrypted using the SPICA-XB algorithm which is a combination of two cryptographic algorithms namely spinning caesar and binary XOR.